2018
DOI: 10.1519/ssc.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Practical Applications of Water Immersion Recovery Modalities for Team Sports

Abstract: COLD THERAPIES ARE WIDELY USED MODALITIES TO ENHANCE RECOVERY WITHIN AN ATHLETIC POPULATION IN ADDITION TO OTHER ESSENTIAL COMPONENTS OF RECOVERY. ALTHOUGH THE BENEFITS OF COLD THERAPIES ARE DOCUMENTED IN THE SCIENTIFIC LITERATURE, RECENT RESEARCH HAS DEMONSTRATED SOME POTENTIAL HARMFUL EFFECTS OF SUCH MODALITIES AS WELL AS INDIVIDUAL RESPONSES TO SIMILAR PROTOCOLS. THIS ARTICLE REVIEWS THE CURRENT KNOWLEDGE ON THE DIFFERENT PROTOCOL CHARACTERISTICS AND INDIVIDUAL FACTORS THAT MAY CONTRIBUTE TO RESPONSES OF CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…The differences in methodologies used (e.g., participants, training frequency, intensity, and duration of CWI) make it difficult to compare between studies. Therefore, we would suggest that further research is needed to provide practical applications to highly-trained team sport athletes, and that understanding the intensity of the training, the density of the week, the athletes' individual goals and the requirements during the season will provide the rational for the implementation of CWI (Tavares et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…The differences in methodologies used (e.g., participants, training frequency, intensity, and duration of CWI) make it difficult to compare between studies. Therefore, we would suggest that further research is needed to provide practical applications to highly-trained team sport athletes, and that understanding the intensity of the training, the density of the week, the athletes' individual goals and the requirements during the season will provide the rational for the implementation of CWI (Tavares et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…lower CWI temperatures for subjects with a greater BSA:BM and fat mass), then the beneficial effects of CWI on recovery could be increased. 30…”
Section: Discussionmentioning
confidence: 99%
“…Although water temperatures might not be the main factor contributing to the beneficial effects observed after contrast water therapy [ 8 ], the too-small difference in cold (15 °C) and hot (37°) water temperatures might partly explain our results. In a recent review Tavares et al [ 30 ] suggested that there might be an ideal zone for water temperature during cold water immersion (between 11 and 15 °C); Sanchez-Urena reported hot water temperatures between 38 and 42 °C [ 15 ]. Indeed, the expected “vasomotion” requires real changes (temperature, pressure) that are hardly achievable with 90 s immersion periods.…”
Section: Discussionmentioning
confidence: 99%